Minimalistic hybrid approach for the percutaneous treatment of chronic coronary total occlusions: An in‐depth analysis of the whole algorithm. Issue 4 (28th July 2022) - Wilgenhof, Adriaan; Vescovo, Giovanni Maria; Bezzeccheri, Andrea; Scott, Benjamin; Vermeersch, Paul; Convens, Carl; Verheye, Stefan; Zivelonghi, Carlo; Agostoni, Pierfrancesco
Abstract: Introduction: The minimalistic hybrid approach (MHA) is an algorithm to perform chronic total occlusion (CTO) percutaneous coronary intervention (PCI). The current study aims to evaluate the distribution of patients among the five different treatment strategies, the different techniques used in each strategy, the overall procedural success, and the safety of the MHA algorithm. Methods: Data from a consecutive series of patients with a CTO who underwent elective PCI between February 2019 and July 2021 were prospectively collected and retrospectively analyzed. Results: One hundred and forty‐three CTOPCI in 135 patients were approached according to the MHA algorithm: 134 CTO (93.7%) were successfully recanalized and 9 procedures failed. About half of the procedures (48.3%) were approached using strategy A: antegrade "blind wiring" with contralateral retrograde options, making this the most popular strategy. A total of 89 procedures (62.2%) were completed with a single guiding catheter; in 86 (96.6%) a forearm approach was used. The remaining 54 cases were performed with dual access; in the majority of these patients (90.7%), a bilateral forearm approach was used. The only reason to use the femoral access was inadequate forearm access. One hundred and fifty‐four out of 197 (78.2%) access sites were 6 French sheaths. Conclusion: MHA is a stepwise approach focused on the forearm approach to reduce the number of access sites and catheter size used in CTOPCI while maintaining proficiency and safety. Operators should be warned that this approach should be adopted only by experienced CTO operators who master all the strategies of the classic hybrid algorithm and the forearm approach.